Understanding Employee Loyalty: Motivation and Compensation in the Indonesian Garment Sector - Retnowati, Ayu Nike; Hafizhah , Salsabila; Putra, Okta Eka (Commercium : Journal of Business and Management, 2025)
This study investigates the influence of motivation and compensation on employee loyalty at CV. Garmen XYZ, a garment company facing a high employee turnover rate (up to 13.8%) and above-average absenteeism (7.1%). These issues reflect low employee loyalty, potentially affecting productivity and organizational stability. Furthermore, compensation remains below the regional minimum wage, and absenteeism indicates low employee motivation. The study aims to examine the conditions of motivation, compensation, and loyalty, and to measure the partial and simultaneous influence of motivation and compensation on loyalty. A quantitative approach was applied using descriptive and verification methods. Data were collected from 104 respondents through closed questionnaires using a Likert scale, selected via purposive sampling. Validity and reliability tests were conducted, followed by classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²). Results show that motivation, compensation, and employee loyalty are generally perceived as high. However, real conditions reveal a mismatch, with compensation below standards and high turnover. Motivation has a significant partial influence on loyalty (64.8%), while compensation does not, though it contributes 33.5%. Simultaneously, motivation and compensation significantly influence employee loyalty, with a combined effect of 64.4%. The findings highlight that enhancing motivation is more effective in fostering employee loyalty than relying on compensation alone.